The Criterion of the Sun’s Height in the Determination of Early Fajr Time of Jurisprudence and Astronomical Perspectives - Malo, Erina Putri; Wakia, Nurul; Alimuddin (HISABUNA: Jurnal Ilmu Falak, 2023)
The use of early dawn criteria in Indonesia varies from 15,17,18,19 and 20 degrees both in terms of jurisprudence and astronomy. The purpose of this study was to determine the height of the sun in astronomy, to find out the urgency of the early prayer times from the perspective of fiqh and to find out the fiqh and astronomy reviews of the criteria for the height of the sun in determining the start of the time for the dawn prayer. The type of research used is literature with a syar’i and astronomical approach and is equipped with secondary and primary data, the data collection method is documentation. The results showed that the position of the sun 20 degrees below the horizon in Indonesia is used as ijtihad, based on sulfur and astronomical reasoning which is considered valid. Saadoeddin Djambek is the originator of 20 degrees as a criterion for dawn and is currently used by the Ministry of Religion. The difference in criteria in Indonesia is considered reasonable, all the criteria for dawn used are correct depending on the place of observation and the observation technique. The implication of this research is that different parties will study in more detail at the beginning of time so as not to cause problems or disputes in determining the time of dawn. In order to unite the understanding of each group from an early age, so that there are no more differences in Islamic society in the future, it is necessary to carry out research that is repeated, transparent and sustainable, as well as a comprehensive method so that the search becomes valid and no longer asked questions. And the information obtained after the observation must be transparent so that it can be used as a reference for observations and criteria for the height of the sun in determining the time of sunrise. Keywords: Sun’s altitude, Dawn Time, and Jurisprudence & Astronomy point of view.